Enhancing the performance of random lasers: Effects of Localised Surface Plasmons and Resonance Energy Transfer - Dawes J.M.; Ismail W.Z.W.; Goldys E.M.; Coutts D.W. (SciTePress, 2024)
Indexed by SCOPUS